Targeted liquid chromatography–mass spectrometry analysis of serum acylcarnitines in acetaminophen toxicity in children. (February 2014) - Bhattacharyya, Sudeepa; Yan, Ke; Pence, Lisa; Simpson, Pippa M; Gill, Pritmohinder; Letzig, Lynda G; Beger, Richard D; Sullivan, Janice E; Kearns, Gregory L; Reed, Michael D; Marshall, James D; Van Den Anker, John N; et al.
Aim: Long-chain acylcarnitines have been postulated to be sensitive biomarkers of acetaminophen (APAP)-induced hepatotoxicity in mouse models. In the following study, the relationship of acylcarnitines with other known indicators of APAP toxicity was examined in children receiving low-dose (therapeutic) and high-dose ('overdose' or toxic ingestion) exposure to APAP.Materials & methods: The study included three subject groups: group A (therapeutic dose, n = 187); group B (healthy controls, n = 23); and group C (overdose, n = 62). Demographic, clinical and laboratory data were collected for each subject. Serum samples were used for measurement of APAP protein adducts, a biomarker of the oxidative metabolism of APAP and for targeted metabolomics analysis of serum acylcarnitines using ultra performance liquid chromatography–triple-quadrupole mass spectrometry.Results: Significant increases in oleoyl- and palmitoyl-carnitines were observed with APAP exposure (low dose and overdose) compared with controls. Significant increases in serum ALT, APAP protein adducts and acylcarnitines were observed in overdose children that received delayed treatment (time to treatment from overdose >24 h) with the antidote N -acetylcysteine. Time to peak APAP protein adducts in serum was shorter than that of the acylcarnitines and serum ALT.Conclusion: Perturbations in long-chain acylcarnitines in children with APAP toxicity suggest that mitochrondrial injury and associated impairment in the β-oxidation of fatty acids are clinically relevant as biomarkers of APAP toxicity.